Reactive oxygen signalling: the latest news - Laloi, C.; Apel, K; Danon, A.
During the past two years, a wide range of plant responses have been found to be triggered by hydrogen peroxide that is generated in a genetically controlled manner by NADPH oxidases. Several studies have revealed examples of how changes in the concentrations of reactive oxygen species (ROS)are perceived and transferred into signals that change the transcription of genes. Moreover, both the chemical identity of a given ROS and the intracellular site of its production seem to affect the specificity of its biological activity, further increasing the complexity of ROS signalling within plants.
Keywords: ABA, ABSCISIC ACID; AOX, ALTERNATIVE OXIDASE; ATMPK3, ARABIDOPSIS THALIANA MAPK3; ATNDPK2, ARABIDOPSIS THALIANA NUCLEOTIDE DIPHOSPHATE KINASE2; FLU, FLUORESCENT; MAPK, MITOGEN-ACTIVATED PROTEIN KINASE; 1O2, SINGLET OXYGEN; OST1, OPEN STOMATA1; NPR1, NON-EXPRESSOR OF PR1; PCD, PROGRAMMED CELL DEATH; PR, PATHOGENESIS-RELATED; PTP; PROTEIN TYROSINE PHOSPHATASES; RBOH; RESPIRATORY BURST OXIDASE HOMOLOGUE; ROS; REACTIVE OXYGEN SPECIES; SA; SALICYLIC ACID; SAR; SYSTEMIC ACQUIRED RESISTANCE; TGA1; TGACG-SEQUENCE-SPECIFIC BINDING-PROTEIN1; TF; TRANSCRIPTION FACTOR; TRANSCRIPTION FACTOR; THIOREDOXIN-2